EFEKTIVITAS TERAPI SAPU JAGAD TERHADAP PENURUNAN SKALA NYERI PADA LANSIA DI UPT PANTI WERDHA MOJOPAHIT MOJOKERTO - Himawan, Dika; Mahmudah, Rifaatul Lailah; Fatmawati, Atikah (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
One of the changes that occur in the elderly is pain. Pain is a problem in the elderly that difficult to handle and can have an impact on the decline in physical functional ability. The purpose of this study is to analyze the effectiveness of broom therapy jagad to decrease the scale of pain in the elderly at UPT Panti Werdha Mojopahit Mojokerto.The design in this study used Quasy Experimental with one group serial pretest and posttest design with random sampling technique with the number of samples of 21 respondents. The measuring tool that used is the VAS (Visual Analog Scale) questionnaire. This study was conducted for four weeks from February 19, 2018 to 19 March 2018. document were analyzed using paired T-test and independent T-test. The results of this study indicate that most respondents who experience relaxed or no pain as much as 9 respondents with percentage (42.85%) and respondents who experienced mild pain as much as 12 respondents with percentage (57.15%). Based on the result of paired t-test was obtained a significant number is 0,00 cause the significance is (p) <0.05 then H1 accepted wich mean that there is effectiveness of broom therapy jagad to decrease the scale of pain in elderly at UPT nursing werdha mojopahit mojokerto. Broom therapy jagad is one of alternative non-pharmacology therapy that can be used to reduce pain by strengthening the muscles and accelerate blood circulation. Broom therapy jagad can reduce the level of pain in the elderly, so this theraphy becomes one form of non-pharmacology therapy that can be done safely and efective with simple methods and tools. It is concluded that there is influence of broom therapy jagad to level of pain in elderly at UPT of werdha mojopahit mojokerto.Keywords:Sapujagad Therapy, Pain, Elderly.